Real-coded genetic algorithm for parametric modelling of a TRMS - Toha, Siti Fauziah; Tokhi, Mohammad Osman (2009)
This paper present a novel and scrutinized parametric modeling of a laboratory scale helicopter, a twin rotor multi input multi output system (TRMS), by employing a real-coded genetic algorithm (GA) technique. The main goal of this work is to emphasise the potential benefits of this architecture for real system identification. Instead of working on the conventional bit by bit operation, both the crossover and mutation operators are real-valued. The effectiveness of the proposed algorithm is demonstrated in comparison to a binary-coded GA in modelling the TRMS. A complete system identification procedure has been carried out, from experimental design to model validation using a laboratory-scale helicopter. In this case, the identified model is characterized by a fourth order linear ARMA structure which describes with very high precision the hovering motion of a TRMS. The TRMS can be perceived as a static test rig for an air vehicle with formidable control challenges. Therefore, an analysis of modeling of nonlinear aerodynamic function is needed and carried out in both time and frequency domains based on observed input and output data. Experimental results are obtained using a laboratory set-up system, confirming the viability and effectiveness of the proposed methodology.